Investasi Asing Melimpah di Tengah Institusi Yang Buruk di Tiongkok - Arisanto, Puguh Toko (Nation State: Journal of International Studies, 2020)
China has become the world's second largest FDI destination in recent years, despite its poor institution status. The success of China seems to undermine the existing theoretical paradigm that good institutions are significantly determinant factors to attract FDI.  This paper aims to explain three locational advantages possessed by China which are domestic market, relatively low wages and broad global market access as attracting factors to FDI inflow amid poor institutions. Furthermore, this paper will explain correlation of FDI with poor institutions in China from some elements of governance.